2016
DOI: 10.1111/jce.13122
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome of Left Atrial Voltage‐Guided Substrate Ablation During Atrial Fibrillation: A Novel Adjunctive Ablation Strategy

Abstract: Patients with LVA had an equally favorable long-term ablation outcome compared to those without. As an adjunct to PVI, voltage-guided substrate modification may be an important ablation strategy in patients with LA structural remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
85
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 41 publications
3
85
0
2
Order By: Relevance
“…Intrinsically, all LVAs may not always be ablated for the modification. This study also indicated that the LVAs after the PVI were not an independent predictor for AF recurrence as described previously . Excessive lesion sets for substrate modification may lead to totally new atrial arrhythmias .…”
Section: Discussionsupporting
confidence: 83%
“…Intrinsically, all LVAs may not always be ablated for the modification. This study also indicated that the LVAs after the PVI were not an independent predictor for AF recurrence as described previously . Excessive lesion sets for substrate modification may lead to totally new atrial arrhythmias .…”
Section: Discussionsupporting
confidence: 83%
“…Different study groups reported lower success rates of AF ablation procedures in women . Delayed referrals and therefore a higher age and comorbidity were discussed . In our BIFA population, females were also older (70.1 ± 6.1 vs. 66.4 ± 8.7, P = 0.026), so a somewhat advanced atrial disease would be possible if progression is assumed.…”
Section: Discussionmentioning
confidence: 84%
“…Yagishita et al. reported about 60% of PAF patients showing some type of low voltage areas, with good results after substrate based ablation; however, in this study group EAVM was performed during AF …”
Section: Discussionmentioning
confidence: 99%
“…In many patients with AF, individually located sites and/or patchy fibrotic areas targeted specifically for ablation have been found. However, in some patients with AF having diffuse, massive fibrosis, there seem to be no apparent curative ablation approaches . The approaches include ablative homogenization of the LVAs, encircling of the LVAs for isolation, and linear lesions from the isolated LVAs connecting them to anatomic structures to prevent AT .…”
Section: Discussionmentioning
confidence: 99%